The Effects Of Fructose-Induced Metabolic Syndrome On Renal Haemodynamic And Excretory Function In Rat - Abdulla, Mohammed H. (2012)
This study investigated whether the α1-adrenoceptor responsiveness of the renal vasculature was altered in a metabolic syndrome state due to high-fructose feeding. Male Sprague-Dawley rats were fed for 8 weeks with 20% fructose in the drinking water (F), while their controls received tap water (C) to drink ad libitum. Metabolic, functional and haemodynamic parameters were assessed weekly and at the end of the study. In another set of rats, F received either carvedilol (FCV) or losartan (FL) at (10mg/kg/day po) for 3 weeks starting from week 5 of the experiment. Another group of rats received tempol, a superoxide dismutase mimetic (FT) at (1 mmol/L) with 20% fructose in drinking water for 8 weeks. At the end of the treatment period, an intravenous insulin glucose tolerance test was performed to assess insulin sensitivity. Moreover, rats were pentobarbitone anaesthetized and the reductions in renal cortical blood flow induced by intrarenal administration of noradrenaline (NA), phenylephrine (PE), methoxamine (ME) and angiotensin II (Ang II) were determined in the presence and absence of 5-methylurapidil (5-MU), chloroethylclonidine (CEC) or BMY 7378. Data, mean±SEM were subjected to ANOVA with significance at P<0.05. At the end of the 8 weeks, F had higher systemic blood pressure, plasma glucose, triglycerides and insulin levels but significantly lower absolute and fractional sodium and potassium excretion as compared to C. The F rats expressed reduced (P<0.05) renal vascular responses to NA, PE, ME and Ang II compared to C. The response to Ang II was significantly attenuated by 5-MU, CEC and BMY 7378, and also following carvedilol, losartan or tempol treatments in the F and C rats.